Plan de logística para el fortalecimiento de la cadena de suministros de la empresa Wasipungo - Villacis, David S. (2019)
The business activities in Ecuador related to the commercialization of textile products are objects of demand due to the diversity of customers and the consequent fulfillment of requirements that support the increase of sales and the positioning in the market. Under this guidance, logistics is a relevant aspect of the business economic activity and in this case, WASIPUNGO is aware of the need to control the processes associated with the supply chain in order to improve its performance. The continuous increase in market competitiveness motivates organizations to determine and implement an effective analysis, control and improvement of their processes. Consequently, this research work focuses on the logistics currently available to the establishment in terms of identifying findings that can be improved under a strategic business plan that is sustained and sustainable in the short, medium and long term. In a complementary manner, the WASIPUNGO Company aims to find efficient and effective satisfaction rates for the organization and for its customers, differentiating itself from its competitors based on a quality service that supports increasing its client base in the local market and even expanding its business horizons.